K-means algorithm and multicriteria analysis to determine drainage zones in a geographic region - Peralta Castañeda, Julio César (2023)
This research work presents the results of the external analysis of the problem of the management of the lower Moche river basin in the valley of the same name. These results are framed in the construction of a multicriteria objetive function, to determine a partition of the basin in particular study zones calleded cluster. The objetive function involves the main hydrogeological parameters and some external parameters such as coefficients that involve socio-political criteria and some too specific such as evapotranspiration of different types of plants cultivated in the valley on the underground aquifer.